Electrically evoked late latency response using single electrode stimulation and its relation to speech perception among paediatric cochlear implant users - Saravanan, Palani; Devi, Neelamegarajan; Geetha, Chinnaraj (Frontiers in Human Neuroscience, 2024)
Introduction: Aided auditory late latency responses (LLR) serve as an objective tool for evaluating auditory cortical maturation following cochlear implantation in children. While aided LLR is commonly measured using sound-field acoustic stimulation, recording electrically evoked LLR (eLLR) offer distinct advantages, such as improved stimulus control and the capability for single electrode stimulation. Hence the study aimed to compare eLLR responses with single electrode stimulation in the apical, middle, and basal regions and to evaluate their correlation with speech perception in paediatric cochlear implant (CI) recipients.Method: eLLR responses with single electrode stimulation were measured in 27 paediatric unilateral CI users with an active recording electrode placed at Cz. The stimuli consisted of 36 msec biphasic pulse trains presented across three electrode sites (apical-E20, middle-E11, and basal-E03). eLLR responses were compared across these electrode sites, and the relationship between speech recognition scores in quiet and age at implantation with eLLR components was evaluated.Results: eLLR responses were detected in 77 out of 81 tested electrodes (27 for apical, 26 for middle, and 24 for basal stimulation). Of all the participants combined, there were no significant differences in P1, N1 latencies and P1 amplitude across electrode sites. However, significantly larger N1 and P1-N1 amplitudes were observed for apical stimulations compared to basal stimulations. No differences in N1 amplitude were found between middle and apical stimulations, and the P1-N1 amplitude was significantly larger for middle compared to basal electrode stimulation, with no difference between the apical and middle electrodes stimulation.A moderate positive correlation was present between speech recognition scores in quiet and both N1, P1-N1 amplitudes for apical stimulation. Age at implantation was negatively correlated with N1 amplitude for the apical and P1-N1 amplitude for basal stimulation.Discussion: eLLR responses could be elicited in majority of paediatric CI users across electrode sites. Variations in eLLR responses across electrode sites suggest disparities in auditory cortical maturation. The findings underscore the significance of the N1 biomarker in evaluating higher-order auditory cortical development. Therefore, utilizing eLLR with single electrode stimulation may serve as a valuable tool for assessing post-cochlear implantation maturational changes in paediatric populations.